Reflecting on Islam in America: July 5- 7, 2002 • Chicago, Illinois (American Journal of Islam and Society, 2002)
"The strength of America is in its diversity, and this diversity includes theIslamic component, which is part of the American mainstream now." Soproclaimed ISNA secretary general Sayyid M. Syeed while inauguratingthe sixth annual ISNA Islam in America Conference, which is now part ofthe American academic calendar.Held in Chicago on July 5-7, four conferences were featured: Islam inAmerica, Islam among Latino Americans, Islam in American Prisons, andMuslim Refugee Resettlement in America. The mainstream American mediawas there in full to cover these events.l n his inaugural address, Syeed said that Muslims must continue toshape their public identity as they further integrate into mainstreamAmerican society. He added that while public perceptions about Muslimsand Islam have improved over the last 30 years, there is still work to bedone. He stated that ISNA will continue to serve Muslim Americans andpromote understanding among all Americans, and that INSA has receiveda federal faith-based initiative grant for a project.Mary Ann Peters, American ambassador to Bangladesh, remarked inher keynote address that America derives its strength from diversity andstressed that there is no acceptable level of intolerance in America. Sheinformed the audience that she had reached out to over 2,000 Bangladeshireligious leaders to promote womens' rights in their country, and that promoting democracy overseas serves American interests. She would like tosee better relations between the U.S. and Muslim countries, and mentionedthat the American government has accepted her suggestion of regularexchanges of religious scholars between the two countries.Shaikh Hamza Yusuf focused on the Prophet's conduct and remindedeveryone that he never repaid persecution, insults, or injury with anger orin kind. Addressing the mainstream media's treatment of Muslims, Yusufsaid that instead of simply criticizing the media, Muslims must form anorganization similar to the Anti-Defamation League that could correct andinform their detractors. Dr. David Schwartz, another keynote speaker whorecently retired as religious services administrator for the Federal Bureau ofPrisons, said that Islam is a positive element in inmates' lives. He vehementlyrejected the insinuation that American prisons are being used as ...